Patterns of Adverse Drug Reactions in the Medical Intensive Care Unit of an Indian Tertiary Care Hospital - T K Ponnuswamy, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Patterns of Adverse Drug Reactions in the Medical Intensive Care Unit of an Indian Tertiary Care Hospital